Including participation requirements into planning law - Daniel Hollemans; Saskia Bisschops; Raoul Beunen (European Journal of Spatial Development, 2025)
This paper analyses how ambitions to enhance participation in spatial planning decisions were translated into the new Environment and Planning Act in the Netherlands that took effect in 2024. The study analysed the various ambitions for enhancing participation and compared the participation requirements before and after the legal reform. The study showed that participation requirements hardly changed. Despite ambitions to enhance participation through new legislation, new rules have been formulated that however do not regulate the content of the participation process beyond the requirement that were into force before the new act took effect. The study shows that the formulation of legal rules concerning participation was strongly influenced by overly optimistic expectations about possible positive effects of participation, while no attention was given to the conditions that are needed to ensure that these positive effects indeed materialise. This makes it debatable that a desired improvement of participation comes about.